Buying behavior of working adult towards car / Mohd Ridzuan Osman - Osman, Mohd Ridzuan (2014)
The purpose of this study is to determine the relationship between the variables of perceived value and the perceived quality towards working adult behavior on buying a car. This study is more focusing on their respondent behavior inclusive of buying behavior of the working adults towards their car preferences. In essence, the data collection had given an insight that working adult's preference on buying a car are based on the quality and perceived value. Furthermore, this study would be an another scope of consumer buying behavior had been explore in marketing research.